Social-psychological determinants of hormonal contraceptive use intentions among adolescent girls in the Bono East Region of Ghana - Ellen Abrafi Boamah-Kaali; Ellen Abrafi Boamah-Kaali; Robert A. C. Ruiter; Seth Owusu-Agyei; Seth Owusu-Agyei; Kwaku Poku Asante; Fraukje E. F. Mevissen; Fraukje E. F. Mevissen (Frontiers Media S.A., 2023)
IntroductionThe correct and consistent use of hormonal contraceptive (HC) methods by sexually active adolescent girls can prevent pregnancy and avert the health and social consequences of unwanted pregnancy for both the mother and her child. Despite these benefits, research shows that HC use is rather low among adolescent girls globally and especially among those in low and middle-income countries. This study was carried out to assess the social-psychological determinants of HC use intentions among adolescent girls and young women.MethodsA cross-sectional survey was conducted among 1,203 young women aged 15-24 years from 70 communities within the Kintampo North Municipality and Kintampo South District in the Bono-East Region of Ghana from April 2021 to September 2021. Multiple linear regression analysis was used to identify factors associated with the intention to use HC among the entire sample of 1,203 respondents and among two sub-samples of young women based on HC use experience.ResultsAttitude toward personal HC use (β = 0.268; p < 0.001), self-efficacy toward access and use of HC (β = 0.341; p < 0.001), and HC use experience (β = 0.647; p < 0.001) were found to be significant and unique correlates of HC use intention among the entire sample of adolescent girls. Attitude toward personal HC use and self-efficacy toward access and use of HC were also associated with HC use intention in the two sub samples significantly (p's < 0.001). In addition, among participants with no HC experience, being a Christian as opposed to participants that affiliate themselves with Islam, Traditional religion or being non-religious positively predicts future HC use (β = 0.230; p < 0.01).ConclusionOur results demonstrate that different groups of adolescent girls need different interventions, focusing on different determinants for the motivation to use HC. Comprehensive sexuality education, informing all adolescent girls about the personal benefits of HC use and enhancing their skills in accessing and using HCs, can support their HC use intentions to promote their reproductive health and general wellbeing.